Field relations, age, and tectonic setting of metamorphic and plutonic rocks in the Creignish Hills – North Mountain area, southwestern Cape Breton Island, Nova Scotia, Canada - White, Chris; Barr, Sandra; Davis, Donald; Swanton, David; Ketchum, John; Reynolds, Peter (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2016)
ABSTRACT The Creignish Hills and North Mountain areas of southwestern Cape Breton Island consist mostly of Neoproterozoic rocks typical of the Ganderian Bras d’Or terrane. U-Pb ages presented here for detrital zircon in the Blues Brook Formation of the Creignish Hills confirm a depositional age no greater than about 600 Ma. Although it is possible that some components of the formation are much older, similarities in rock types and field relations suggest that this is not the case. It is likely that the equivalent Malagawatch Formation of the North Mountain area, as well as high-grade metasedimentary rocks of the Melford Formation and Chuggin Road complex in the Creignish Hills and Lime Hill gneiss complex in the North Mountain area, represent the same or stratigraphically equivalent units as the Blues Brook Formation. The minimum ages of all of these units are constrained by cross-cutting syn- and post-tectonic plutons with ages mostly between 565 and 550 Ma, indicating that sediments were deposited, regionally metamorphosed, deformed, and intruded by plutons in less than 40–50 million years. The assemblage of pelitic, psammitic, and carbonate rocks indicates that a passive margin in a tropical climate was quickly changed to an active Andean-type continental margin in which voluminous calcalkaline dioritic to granitic plutons were emplaced. This sedimentary and tectonic history is characteristic of the Bras d’Or terrane and is shared by its likely correlative, the Brookville terrane in southern New Brunswick.